2016
DOI: 10.1071/rd14219
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA expression of selected pro-inflammatory factors in inflamed bovine endometrium in vivo as well as in endometrial epithelial cells exposed to Bacillus pumilus in vitro

Abstract: Endometrial epithelium plays a crucial role in the first immune response to invading bacteria by producing cytokines and chemokines. The aim of this study was to investigate the first inflammatory response of the endometrium in vivo and in vitro. Gene expression of several pro-inflammatory factors and Toll-like receptors (TLR2, -4, -6) was determined in endometrial cytobrush samples obtained from healthy cows and cows with clinical or subclinical endometritis. Endometrial epithelial cells were co-cultured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 71 publications
1
20
1
1
Order By: Relevance
“…Three weeks after the intrauterine administration of L. buchneri DSM 32407 or the placebo, the mRNA of CXCL1 / 2, CXCL3 , CXCR2 , IL1B , IL8 and PTPRC was lower expressed in the LAC / SCE group compared with the PLA/SCE group. These pro-inflammatory factors were higher expressed in cows with signs of SCE and/or CE and thereby related to uterine health problems in a recent study at the same time point 24 and in previous studies at earlier time points of the puerperium 21 , 23 , 33 . The mRNA data of the present study thereby indicates that the endometrial immune system of cows treated with L. buchneri is downregulated three weeks after its administration to the uterus.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Three weeks after the intrauterine administration of L. buchneri DSM 32407 or the placebo, the mRNA of CXCL1 / 2, CXCL3 , CXCR2 , IL1B , IL8 and PTPRC was lower expressed in the LAC / SCE group compared with the PLA/SCE group. These pro-inflammatory factors were higher expressed in cows with signs of SCE and/or CE and thereby related to uterine health problems in a recent study at the same time point 24 and in previous studies at earlier time points of the puerperium 21 , 23 , 33 . The mRNA data of the present study thereby indicates that the endometrial immune system of cows treated with L. buchneri is downregulated three weeks after its administration to the uterus.…”
Section: Discussionmentioning
confidence: 59%
“…Primers named CXCL1/2 are specific for CXCL1 as well as for CXCL2 33 . At E4 , CXCL1/2 and CXCL3 mRNA was seven- and threefold more highly expressed in the PLA / SCE group compared with the LAC / SCE group, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the cited studies suggest that common pathogens associated with metritis and clinical endometritis do not have a significant role in the SE pathogenesis. It has been suggested that SE may be a response to unspecific uterine infections [19] or a prolonged inflammatory process that persists after bacterial elimination.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…In order to test if strain LMM-1652 T possesses any pathogenic potential, its cytotoxicity was tested in vitro using primary bovine endometrial epithelial cells, as described previously [33]. In brief, primary cells were prepared up to the second passage and were infected with strain LMM-1652 T in different multiplicities of infection (MOIs) and cell viability was assessed by using 0.5 % trypan blue (Sigma-Aldrich).…”
mentioning
confidence: 99%